What is a Trophic Cascade?. (November 2016) - Ripple, William J.; Estes, James A.; Schmitz, Oswald J.; Constant, Vanessa; Kaylor, Matthew J.; Lenz, Adam; Motley, Jennifer L.; Self, Katharine E.; Taylor, David S.; Wolf, Christopher
Abstract : Few concepts in ecology have been so influential as that of the trophic cascade. Since the 1980s, the term has been a central or major theme of more than 2000 scientific articles. Despite this importance and widespread usage, basic questions remain about what constitutes a trophic cascade. Inconsistent usage of language impedes scientific progress and the utility of scientific concepts in management and conservation. Herein, we offer a definition of trophic cascade that is designed to be both widely applicable yet explicit enough to exclude extraneous interactions. We discuss our proposed definition and its implications, and define important related terms, thereby providing a common language for scientists, policy makers, conservationists, and other stakeholders with an interest in trophic cascades. Trends: The notion of trophic cascades has evolved from a foundational concept in ecology to one that helps define modern goals for conserving and managing ecosystems. The term 'trophic cascade' has grown into a modern lexicon of inconsistent definitions that obscures clear meaning. We propose that trophic cascades specify the effects of predators that propagate downward thorough food webs across multiple trophic levels. Trophic cascades can be triggered by consumptive interactions between predators and prey and nonconsumptive effects due to perceived predation risk by prey. Various 'knock-on effects', initiated by trophic cascades and propagating laterally or upward from the main interaction chain, should not be thought of as part of the trophic cascade.